PUBLIC ACCEPTANCE OF GREY WATER REUSE: A CASE STUDY & ANALYSIS IN THE UAE: Received:24th December 2020; Revised:19th February 2021, 13th March 2021, 20th April 2021; Accepted:29th May 2021 - Abdelrahman, Bassant; Fattah, Kazi (MATTER: International Journal of Science and Technology, 2021)
Fresh water is considered a limited resource in the United Arab Emirates (UAE), with full reliance on ground water and desalinated saline water. Grey water reuse has been investigated as a solution to reduce the demand for potable water and to provide an alternative water resource. However, public perceptions and acceptance of treated wastewater is a significant factor for adopting grey water reuse on a wide domestic scale. This study aims to investigate the factors influencing public acceptance of grey water reuse. A stated preference survey is designed and distributed in the different Emirates of the UAE. The results of the study suggest that there is still a lack of awareness in the perception of fresh water availability among residents in the UAE. Moreover, 70 % of the surveyed sample agreed to use treated grey water in applications not involving direct contact. Factors influencing public acceptance were found to be health risk concerns, lack of confidence in the water quality, lack of scientific knowledge about the treatment process and the potential uses of treated grey water. The results of this study demonstrate the potential for the public acceptance of grey water reuse, thus, its implementation in the UAE.